Checklist of marine Bivalvia (Mollusca) from Brazil, with descriptive analyses of their bathymetric and geographical distribution - Passos, Flávio Dias; Batistão, Alan Rodrigo; Lima, Luan Lucas Cardoso (Zootaxa, 2024)
After revising the literature and consulting the pertinent virtual databases, we here list all Brazilian marine bivalves currently considered as valid and include data on their geographical and bathymetrical distribution. The list contains 516 indigenous and nine introduced species. Among the former, 461 species are autobranchs and 64 are protobranchs. They belong to 42 superfamilies, nine of them containing at least 20 species each; there are 77 families, twelve of which contain at least 15 species; most of these more speciose groups are typical from shallow waters (e.g., Tellinoidea and Veneroidea) and/or have been reviewed taxonomically (Nuculanoidea and Cuspidarioidea). There are 368 species which live exclusively on the continental shelf, 86 are only known from deep water and 68 species have a wide bathymetric distribution. More than half of the 368 continental-shelf species have a wide geographic distribution; 40 species are exclusive to the Brazilian province, the others also occur in the Caribbean and/or Argentine shelf waters; those from the Caribbean need more investigation. Important knowledge gaps remain for Brazilian Galeommatoidea and Nuculoidea, deep-sea species of Mytilidae, Teredinidae, and Arcidae; the Poromyidae, Limopsidae, Propeamussiidae, and Thyasiridae appear to be underrepresented. Compared to 29 world regional faunas of marine bivalves, the Brazilian diversity ranks in the ninth position.